Living and neighborhood environments and anxiety symptoms among older adults in Anhui, China: evidence from a cross-sectional study - Jingya Zhang; Chen Dai; Qing Wang; Wenzheng Zhao; Guodong Shen; Jing Cheng; Ren Chen; Yan Zhang (BMC Public Health)
Abstract Objective This study aims to investigate the relationships between living and neighborhood environmental factors and anxiety symptoms among older adults residing in urban and rural areas of Anhui Province, China. Methods Data were collected from 5876 participants in a cross-sectional study carried out in four cities located in Anhui, China. Anxiety symptoms were evaluated via the Generalized Anxiety Disorder scale (GAD-7), and participants with scores of 5 and above were defined as having anxiety symptoms. The presence of dust and noise in the context of daily life was used to evaluate the living environment of the participants. The neighborhood environment was assessed by the availability of barrier-free facilities, proximity to facilities (supermarkets, restaurants, hospitals, and parks), and green and blue space near participants’ dwellings. Multilevel linear and logistic regression analyses were used to estimate the associations between these environmental factors and anxiety symptoms. Results The participants who lived in dusty environments had elevated GAD-7 scores and higher odds of anxiety (dust: β = 0.754, 95% CI: 0.337, 1.171; OR = 1.451, 95% CI: 1.164, 1.809). Having barrier-free facilities and the existence of a neighboring park decreased the GAD-7 scores and the likelihood of having anxiety symptoms (barrier-free facilities: β=-0.503, 95% CI: -0.992, -0.085; OR = 0.768, 95% CI: 0.656, 0.899; park: β=-0.478, 95% CI: -0.830, -0.125; OR = 0.599, 95% CI: 0.440, 0.816). However, participants residing in close proximity to the hospital presented an increased likelihood of experiencing anxiety symptoms (OR = 1.377, 95% CI: 1.162, 1.631). Conclusions Participants who lived in dusty and noisy environments were more likely to suffer from anxiety, whereas those who lived near barrier-free facilities and parks were at lower risk. The findings emphasize the need for targeted interventions to create age-friendly communities, suggesting an integrated approach that combines environmental health strategies with mental health strategies for older adults.